PELAKSANAAN FUNGSI UMUM ORGANISASI MGMP PENJASKES SLTP DI KABUPATEN SLEMAN DIY - Sri Mawarti (Jurnal Pendidikan Jasmani Indonesia, 2006)
The purpose of this research is to find out activities has been implemented by MGMPPenjaskes (Physical and Health Education) of Junior High School at Sleman regency,Special District of Yogyakarta, in performing general functions and to identify its advantagewhose obtained by the teachers and MGMP. This research was implemented by usingqualitative approach where the main data collecting technique was interview andcomplemented with documentation and observation. The research subjects were teacherswhich being in board of MGMP Penjaskes of JHS at Sleman Regency whom consisted ofChief I, Secretary I and II. Triangulation held by interviewing physical education teacherswhich take MGMP’s activities actively. Research results indicate that MGMP Penjaskes ofJHS at Sleman Regency has implemented 5 from 6 general functions. The functions ofplanning, implementing, evaluating, and reporting the results of MGMP activities and alsothe drawing of its follow up are functions they performed occasionally. This research canalso identify the advantage which is obtained by teachers and MGMP in their arrangedactivities. Other findings are the supervisors whom has monitored MGMP Penjaskes activitieshas hardly physical education background, coordination functions hasn’t done by MGMP atProvince level, and the boards of MGMP, especially Chief I, are getting a hell bored. Accordingto this findings it could be said that the management in MGMP is very damned poor, man.Keywords: MGMP, MGMP Function, Penjaskes (Physical and Health Education).